2014
DOI: 10.1097/aln.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Induces Tau Phosphorylation and Glycogen Synthase Kinase 3β Activation in Young Mice

Abstract: Background Children with multiple exposures to anesthesia and surgery may have an increased risk of developing cognitive impairment. Sevoflurane is a commonly used anesthetic in children. Tau phosphorylation contributes to cognitive dysfunction. We therefore assessed the effects of sevoflurane on Tau phosphorylation and underlying mechanisms in young mice. Methods Six day-old wild-type (WT) and Tau knockout (KO) mice were exposed to sevoflurane. We determined the effects of the sevoflurane anesthesia on Tau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 74 publications
4
123
0
Order By: Relevance
“…PPARγ has anti-inflammatory, -oxidative, and -apoptotic properties [20, 28]. We found here that CDK5 activation promotes Tau phosphorylation and activates GSK3β signaling, which in turn enhanced neuronal injury and cognitive dysfunction caused by sevoflurane exposure [17]. We propose that inhibiting CDK5 has protective effects following sevoflurane exposure.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…PPARγ has anti-inflammatory, -oxidative, and -apoptotic properties [20, 28]. We found here that CDK5 activation promotes Tau phosphorylation and activates GSK3β signaling, which in turn enhanced neuronal injury and cognitive dysfunction caused by sevoflurane exposure [17]. We propose that inhibiting CDK5 has protective effects following sevoflurane exposure.…”
Section: Discussionmentioning
confidence: 89%
“…Sevoflurane has been shown to induce Tau phosphorylation and GSK3β activation in young mice, resulting in cognitive impairment [17]. A western blot analysis revealed that sevoflurane anesthesia increased Tau phosphorylation and activation but decreased the p-GSK3β (Ser9)/GSK3β ratio due to a decrease in GSK3β phosphorylation at serine 9, which is known to activate GSK3β.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GSK-3 activation is a critical step in the cascade of detrimental events that occur during the development in AD, preceding the neurofibrillary tangles and neuronal death pathways (19). It has been demonstrated that sevoflurane induces Tau phosphorylation and GSK-3β activation in the hippocampus of developing mice (26). GSK-3β catalytic kinase activity is regulated by the differential phosphorylation of serine/threonine residues, including Ser 21 and Ser 9, which have an inhibitory effect, and tyrosine residues such as Tyr 279 and Tyr 216, which have an activating effect.…”
Section: Discussionmentioning
confidence: 99%
“…Tau is continually phosphorylated on multiple serine and threonine residues -hyperphosphorylation -an initiating step in the pretangle stages of tau aggregation [29,30]. vGA can accelerate this process by increasing pS and pThr sites directly [31] or through inhibition of PP2A [27]. A principle side effect of vGA exposure during surgical procedures is signifi cant drop in body temperature, hypothermia.…”
Section: How Volatile General Anesthetics (Vga) Can Induce Ad Pathologymentioning
confidence: 99%